2010
DOI: 10.1038/ejhg.2010.70
|View full text |Cite
|
Sign up to set email alerts
|

The unfolding clinical spectrum of holoprosencephaly due to mutations in SHH, ZIC2, SIX3 and TGIF genes

Abstract: Holoprosencephaly is a severe malformation of the brain characterized by abnormal formation and separation of the developing central nervous system. The prevalence is 1:250 during early embryogenesis, the live-born prevalence is 1:16 000. The etiology of HPE is extremely heterogeneous and can be teratogenic or genetic. We screened four known HPE genes in a Dutch cohort of 86 non-syndromic HPE index cases, including 53 family members. We detected 21 mutations (24.4%), 3 in SHH, 9 in ZIC2 and 9 in SIX3. Eight mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 48 publications
4
28
1
Order By: Relevance
“…These results are consistent with our previous findings for smaller series 1 9 18 34. Point mutations in SHH, SIX3 , and TGIF were highly heritable, with heritabilities of 73%, 88%, and 100%, respectively, whereas most ZIC2 mutations were de novo (70% of cases) 6 20. This may be due to a higher penetrance and the high frequency of severe HPE in individuals with ZIC2 mutations, resulting in the identification of a larger number of sporadic cases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with our previous findings for smaller series 1 9 18 34. Point mutations in SHH, SIX3 , and TGIF were highly heritable, with heritabilities of 73%, 88%, and 100%, respectively, whereas most ZIC2 mutations were de novo (70% of cases) 6 20. This may be due to a higher penetrance and the high frequency of severe HPE in individuals with ZIC2 mutations, resulting in the identification of a larger number of sporadic cases.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, facial morphology in subjects with ZIC2 mutations was generally characterised by moderate facial dysmorphia or even a normal face (category 4), associated with alobar or semilobar HPE. This feature seems to be specific to ZIC2 mutations and has also been reported by other teams 6 20. Solomon et al 6 mentioned a particular facial phenotype found in some of the cases in our series, with a high proportion of abnormal noses (nine cases), usually short, sometimes flat or large, and ear dysplasia (four cases).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Descriptions of common variations (Supplementary Table 1) and NIH mutations (Supplementary Table 2 and 6) including data from Dubourg et al, 2004 [15] and Paulussen et al, 2010 [38] (Supplementary Tables 3 and 4) are based on the SHH NM_000193.2, ZIC2 NM_007129.2, SIX3 NM_005413.2 and TGIF NM_003244.2 reference sequences (Supplementary Data 7). Guidelines for the naming of the sequence variants conform to the recommendations of the human nomenclature committee (www.hgvs.org/mutnomen) and were checked using the Mutalyzer software for the predicted effects on the reference gene (http://www.mutalyzer.nl/2.0/).…”
Section: Methodsmentioning
confidence: 99%
“…20 The evolutionary conservation of these genes and their critical timing of expression is essential for proper embryonic development, since variants in other human zic genes also cause monogenic diseases, for instance ZIC2 causing holoprosencephaly. 21 The ZIC3 gene, however, is the only ZIC gene to be implicated in laterality disorders. Several animal studies have demonstrated the crucial role of ZIC3 expression during gastrulation and axial patterning and the laterality abnormalities created when knocked out.…”
Section: Introductionmentioning
confidence: 99%